Concomitant Proximal and Distal Tibiofibular Joint Dislocation Associated With a Tibial Shaft Fracture. Issue 15 (1st August 2018) - Hwang, John S.; Sirkin, Michael S.; Gala, Zachary; Adams, Mark; Reilly, Mark C.
Abstract : An association exists between tibial shaft fractures and ankle injuries. In addition, although uncommon, an association between tibial shaft fractures and proximal tibiofibular dislocations has also been established. A review of the previous literature resulted in one case report of a complete proximal and distal tibiofibular joint dislocation without fracture of the tibia or fibula. Here, we discuss a case of a complete proximal and distal tibiofibular syndesmotic complex dislocation associated with a tibial shaft fracture. To the best of our knowledge, this is the first report of this injury pattern associated with a tibial shaft fracture.